1999
DOI: 10.3758/bf03211949
|View full text |Cite
|
Sign up to set email alerts
|

Limitations in attending to a feature value for overriding stimulus-driven interference

Abstract: Six experiments were conducted to examine the effect of knowledge of a target for overriding stimulus-driven interference in simple search tasks (Experiments 1-3) and compound search tasks (Experiments 4-6). In simple search when the target differed from nontargets in orientation, a singleton distractor that had an orientation equivalent to that of a target interfered with search for the target. When the singleton distractor was less salient than the target with respect to the target-defining feature, it still… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
77
3
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(96 citation statements)
references
References 32 publications
15
77
3
1
Order By: Relevance
“…Possibly, a less salient distractor only disrupts search if its salience is defined in the same feature dimension as the target. If distractor and target are unique in different dimensions, interference may only occur if the distractor is more salient than the target [for a similar account see Kumada (1999)]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Possibly, a less salient distractor only disrupts search if its salience is defined in the same feature dimension as the target. If distractor and target are unique in different dimensions, interference may only occur if the distractor is more salient than the target [for a similar account see Kumada (1999)]. …”
Section: Discussionmentioning
confidence: 99%
“…Goal-driven control may play a role, but only after attention has been captured by a salient element (Theeuwes 1992;Theeuwes et al 2000). Recently, Kumada (1999) also showed that knowledge of the target identity could not override the effect of the presence of an irrelevant distractor. Kumada (1999) had participants search for a rectangle tilted 458 to the left amongst multiple vertically oriented rectangles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, for targets defined by shape, RTs were slowed when the (color) singleton distractor was present, relative to when it was absent: There was cross-dimensional interference. Asymmetric cross-dimensional interference has subsequentlybeen reported with other dimensions, including color and luminance (Theeuwes, 1991), color and onset (Theeuwes, 1994), and color and orientation (Kumada, 1999). Cross-dimensional interference suggests that selection cannot be constrained solely by top-down factors, since stimuli from a dimension not defined for selection disrupt performance.…”
mentioning
confidence: 99%
“…Here, following Pashler (1988) and many others, we refer to a salient stimulus as a feature singleton or just singleton, as is usually defined by a local contrast on a perceptual dimension, such as color, orientation, motion, or abrupt transients (Hillstrom & Yantis, 1994;Kumada, 1999;Nothdurft, 1993;Theeuwes, 1992;Yantis & Jonides, 1984). Under the first, bottom-up, account, feature singletons capture attention regardless of the attentional state of the observer.…”
mentioning
confidence: 99%